Quantitative aspects of ruminant digestion and metabolism [ - Djikstra, J. [ (Jan)] , 1964-; Forbes, J. M. [ (John Michael)] , 1940-; France, J. (CABI, 2005)
The first edition of this book. Published in 1993, was very well received as providing a comprehensive review of the digestion and metabolism of ruminant animals. Since its publication, much new research has been conducted in the subject and knowledge hs increased.